2021
DOI: 10.1002/2211-5463.13247
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate inhibits TGF‐β‐induced myofibroblast differentiation and activation in human lung fibroblasts in vitro

Abstract: Fenofibrate (FF), a peroxisome proliferator-activated receptor alpha (PPAR-α) agonist and a lipid-lowering agent, can decrease experimental pulmonary fibrosis. However, the mechanisms underlying the anti-fibrotic effect of FF remain unknown. Hence, this study was conducted to evaluate the effects of FF on transforming growth factor-beta (TGF--induced myofibroblast differentiation and activation in lung fibroblasts. The results showed that FF inhibited alpha-smooth muscle actin (α-SMA) and connective-tissue g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Our focus on the effect of anti-hyperlipidemic drugs in the context of asthma progression was the result of several reports indicating that asthma progression with enhanced remodeling of the airways is associated with metabolic dysfunctions, such as obesity or hyperlipidemia, and dysregulation of the function of PPARs [18,49]. Fenofibrate is known as an agonist of PPARα, and its inhibitory effect on bronchial [23], lung [24,50], subretinal [51], and liver [52] fibrosis has been observed. However, little is known about the involvement of another type of peroxisome proliferator-activated receptor, PPARδ, in fibrosis-related processes, especially in asthma subepithelial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our focus on the effect of anti-hyperlipidemic drugs in the context of asthma progression was the result of several reports indicating that asthma progression with enhanced remodeling of the airways is associated with metabolic dysfunctions, such as obesity or hyperlipidemia, and dysregulation of the function of PPARs [18,49]. Fenofibrate is known as an agonist of PPARα, and its inhibitory effect on bronchial [23], lung [24,50], subretinal [51], and liver [52] fibrosis has been observed. However, little is known about the involvement of another type of peroxisome proliferator-activated receptor, PPARδ, in fibrosis-related processes, especially in asthma subepithelial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the effects of clinically used anti-hyperlipidemic drugs on asthma progression are intensively studied [21][22][23]. Fenofibrate, known as a lipid-lowering agent and a peroxisome proliferator-activated receptor-alpha (PPARα) agonist, decreases experimental pulmonary fibrosis (PF) and subepithelial fibrosis in asthma [23,24]. PPARs are part of the hormone receptor superfamily, including PPARα, PPARδ (also called β), and PPARγ, activated by subtype-specific or pan-PPAR agonist ligands that promote their nuclear translocation and regulation of gene transcription by binding to their peroxisome proliferator response elements (PPREs) [25].…”
Section: Introductionmentioning
confidence: 99%
“…7A-C). Accumulating evidence indicated that PPAR-α-independent mechanisms are involved in the pleiotropic effects of FF on various pathophysiological processes (36,37). However, the knockdown of the PPARA gene with siRNA transfection reduced the stimulatory effect of FF on AhR gene transcription, although the AhR gene inhibition by the PPARA siRNA transfection was not statistically significant (P= 0.08) (Fig.…”
Section: Ff Treatment Enhanced Nrf2 Expression By Stimulating Ahr Exp...mentioning
confidence: 93%
“…Treatment with ciprofibrate or pemafibrate promotes peroxisome proliferation and downregulates myofibroblast differentiation of fibroblasts ( 138 , 142 ). Additionally, fenofibrate suppresses TGF-β-induced myofibroblast differentiation independent of PPARα activation by downregulating mitochondrial respiration ( 140 ). Fibrates suppress neutrophil infiltration, increase vascular permeability, and promote inflammatory cytokine production in bleomycin-induced or LPS-induced lung injury models and reduce lung compliance ( 162 164 ).…”
Section: Aging-related Respiratory Diseases and Cellular Senescencementioning
confidence: 99%